Dimethylammonium 2-[(2-oxo-2H-chromen-7-yl)oxy]acetate - Dong, Feng-Xia (International Union of Crystallography, 2011)
In the title salt, C(2)H(8)N(+)·C(11)H(7)O(5) (−), the acetate group is twisted out of the plane of the coumarin ring system with a C—O—C—C torsion angle of 76.3 (2)°. In the crystal, N—H⋯O hydrogen bonds link the cations and anions into chains propagating in [100].